Antithrombotic therapy in adults with ectatic coronary artery disease: a systematic review and network meta-analysis - Alireza Azarboo; Mohammad Shahabaddin Daneshvar; Alireza Sattari Abroy; Ramin Assempoor; Aryan Taghvaei; Ali Nasrollahizadeh; Mohsen Hajiqasemi; Amirhossein Ghaseminejad-Raeini; Kaveh Hosseini (The Egyptian Heart Journal)
Abstract Background Many studies have validated the use of antiplatelet or anticoagulant therapy in coronary artery ectasia (CAE) to reduce major adverse cardiovascular events (MACE); however, it is not completely known which group of these antithrombotic medications is more effective. The purpose of this systematic review and network meta-analysis was to evaluate the efficacy of different anti-thrombotic treatments in adult patients with CAE. Methods This systematic review and meta-analysis followed preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines as well as PRISMA extension statement for reporting of systematic reviews incorporating network meta-analyses and adhered to a registered predetermined methodology noted in the prospective register of systematic reviews (PROSPERO) protocol. Comprehensive searches were conducted until October 2024. Study selection, data extraction, and risk-of-bias assessments were independently performed by two reviewers. The pairwise meta-analysis compared the odds of MACE among patients receiving different antithrombotic therapies versus no treatment. The network meta-analysis (NMA) combined direct and indirect evidence to compare the efficacy of antithrombotic therapies for MACE. Results Our systematic review included 5,039 adult patients suffering from CAE. The odds of MACE were higher in patients with no treatment when compared with those on dual antiplatelet therapy (DAPT) and aspirin monotherapy; although patients on anticoagulation demonstrated a lower incidence of MACE, the difference with the no treatment group did not reach statistical significance. Among various types of interventions in NMA, DAPT was the best in the treatment of CAE. Conclusions Based on the surface under the cumulative ranking curve (SUCRA) value, DAPT is the most effective treatment in the prevention of MACE for CAE patients, followed by aspirin monotherapy and anticoagulant treatment.